Genome sequencing of the NIES Cyanobacteria collection with a focus on the heterocyst-forming clade. (22nd October 2021) - Hirose, Yuu; Ohtsubo, Yoshiyuki; Misawa, Naomi; Yonekawa, Chinatsu; Nagao, Nobuyoshi; Shimura, Yohei; Fujisawa, Takatomo; Kanesaki, Yu; Katoh, Hiroshi; Katayama, Mitsunori; Yamaguchi, Haruyo; Yoshikawa, Hirofumi; et al.
Abstract: Cyanobacteria are a diverse group of Gram-negative prokaryotes that perform oxygenic photosynthesis. Cyanobacteria have been used for research on photosynthesis and have attracted attention as a platform for biomaterial/biofuel production. Cyanobacteria are also present in almost all habitats on Earth and have extensive impacts on global ecosystems. Given their biological, economical, and ecological importance, the number of high-quality genome sequences for Cyanobacteria strains is limited. Here, we performed genome sequencing of Cyanobacteria strains in the National Institute for Environmental Studies microbial culture collection in Japan. We sequenced 28 strains that can form a heterocyst, a morphologically distinct cell that is specialized for fixing nitrogen, and 3 non-heterocystous strains. Using Illumina sequencing of paired-end and mate-pair libraries with in silico finishing, we constructed highly contiguous assemblies. We determined the phylogenetic relationship of the sequenced genome assemblies and found potential difficulties in the classification of certain heterocystous clades based on morphological observation. We also revealed a bias on the sequenced strains by the phylogenetic analysis of the 16S rRNA gene including unsequenced strains. Genome sequencing of Cyanobacteria strains deposited in worldwide culture collections will contribute to understanding the enormous genetic and phenotypic diversity within the phylum Cyanobacteria.